An Innovative Approach for Maximum Recovery of Isoflavones from Glycine max by the Design of Experiments Method - Aleksandra Bibow; Sławomir Dresler; Marta Oleszek (Applied Sciences)
Isoflavones are the main phenolic compounds of soybean that affect its biological activity. The quantity of these valuable compounds extracted from plant material can significantly vary, influenced by the chosen extraction method and the specific extractants employed. Moreover, in cosmetics and pharmacy, the application of non-toxic, eco-friendly solvents is very important. This study aimed to develop the best mixture of extractants to maximize the recovery of individual isoflavones from soybean seeds by optimization of the proportion of three components: ethanol, water, and propanediol. The design of experiments (DOE) method was strategically employed. The extracts were obtained through accelerated solvent extraction and meticulously analyzed for isoflavone content using advanced electrospray ionization–time of flight–mass spectrometry (ESI-TOF-MS) profiling. The predominant isoflavones were daidzin, genistin, malonylgenistin, malonyldaidzin, and malonylglycitin. Our experiment demonstrated that employing three extractants in a balanced 1:1:1 v/v/v ratio resulted in the highest isolation of isoflavones compared to all other mixtures tested. Nevertheless, a detailed exploration of approximate values and utility profiles revealed a more effective composition for extraction efficiency. This optimal mixture features 32.8% ethanol, 39.2% water, and 27.8% propanediol, maximizing the yield of isoflavones from soybean seeds. The innovative use of mixture design and triangular response surfaces has proven to be a powerful approach for developing this superior three-component extraction mixture. This innovative approach not only enhances extraction efficiency but also paves the way for improved processing methods in the industry.